The Relationship Between Job Resources and Resilience, With Work Engagement in Honorary Teachers - Azzahra, Fatma; Salim, Agus (unprimdn.ac.id, 2025)
Honorary teachers play a crucial role in the Indonesian education system, yet they still face various challenges, such as low welfare and uncertain employment status. These conditions have the potential to impact honorary teachers' work engagement. This study aims to analyze the relationship between job resources and resilience on work engagement among honorary teachers in Cilacap Regency. The study used a quantitative approach with a correlational design. Data were collected through a questionnaire measuring job resources, resilience, and work engagement, and then analyzed using multiple regression analysis. The results showed that job resources and resilience have a positive and significant relationship with work engagement. The higher the job resource support received by teachers and the stronger their resilience, the higher their level of work engagement. The analysis showed that job resources contributed 57.92% to work engagement, while resilience contributed 22.78%. These findings confirm that work environment factors and personal characteristics play a significant role in improving honorary teachers' work engagement. This research is expected to serve as a basis for developing policies and interventions oriented towards improving the welfare and work quality of honorary teachers in Indonesia.